(untitled) (Journal of Applied Oral Science, 2015)
In Aggregatibacter actinomycetemcomitans, different serotypes have been described based on LPS antigenicity. Recently, our research group has reported a differential immunogenicity when T lymphocytes were stimulated with these different serotypes. In particular, it was demonstrated that the serotype b of A. actinomycetemcomitans has a stronger capacity to trigger Th1- and Th17-type cytokine production.Objective This study aimed to quantify the expression of different CC chemokines (CCLs) and receptors (CCRs) in T lymphocytes stimulated with the differentA. actinomycetemcomitans serotypes. In addition, the expression of the transcription factors T-bet, GATA-3, RORC2, and Foxp3, master-switch genes implied in the Th1, Th2, Th17, and T-regulatory differentiation, respectively, was analysed in order to determine T-cell phenotype-specific patterns of CCL and CCR expression upon A. actinomycetemcomitans stimulation.Material and Methods Human naïve CD4+ T lymphocytes were obtained from healthy subjects and stimulated with autologous dendritic cells primed with the differentA. actinomycetemcomitans serotypes. The expression levels for the chemokines CCL1, CCL2, CCL3, CCL5, CCL11, CCL17, CCL20, CCL21, CCL25, and CCL28, as well as the chemokine receptors CCR1, CCR2, CCR3, CCR4, CCR5, CCR6, CCR7, CCR8, CCR9, and CCR10 were quantified by qPCR. Similarly, the expression levels for the transcription factors T-bet, GATA-3, RORC2, and Foxp3 were quantified and correlated with the CCL and CCR expression levels.Results Higher expression levels of CCL2, CCL3, CCL5, CCL20, CCL21, CCL28, CCR1, CCR2, CCR5, CCR6, CCR7, and CCR9 were detected in T lymphocytes stimulated with the serotype b of A. actinomycetemcomitans compared with the other serotypes. In addition, these higher expression levels of CCLs and CCRs positively correlated with the increased levels of T-bet and RORC2 when T lymphocytes were stimulated with the serotype b.Conclusion A T-lymphocyte response biased towards a Th1- and Th17-pattern of CCL and CCR expression was detected under stimulation with the serotype b ofA. actinomycetemcomitans.